Complementary role of cardiac CT in the diagnosis and management of mechanical aortic valve thrombosis with a novel low-dose, ultraslow thrombolysis treatment strategy. Issue 1 (17th January 2022) - Senior, Jonathan; Mahoney, Luke; Gangil, Nishant; Khan, Jamal Nasir
Abstract : A 31-year-old man presented to our emergency department with a 3-day history of progressive breathlessness, fatigue and exertional angina. His history included a mechanical aortic valve replacement (mAVR) for rheumatic heart disease at age 19 years. He could no longer afford medication prescription costs and consequently had not taken oral anticoagulation for 2 months. Transthoracic echocardiography (TTE) demonstrated mechanical prosthetic valve obstruction (PVO) and severe left ventricular (LV) systolic dysfunction; however, valve visualisation was limited by mAVR-related artefact. The patient declined transoesophageal echocardiography. Valve haemodynamics failed to improve despite a prolonged course of parenteral anticoagulation. Multidetector cardiac CT scan was performed which confirmed prosthetic valve thrombosis. A novel low-dose, ultraslow thrombolysis regimen was administered to mitigate the associated bleeding and embolic stroke risk. The patient made an excellent recovery and was discharged on day 30, with repeat cardiac CT scan showing complete resolution of mechanical PVO and normalisation of valve and LV function on TTE.